Application of “The nature of science” box event examples to middle school seventh grade students - Özlem Afacan; Demet Şener Çanlı (International Journal of Evaluation and Research in Education (IJERE), 2019)
Previous study on the nature of science indicated that the use of activities is essential and important in the teaching of the nature of science subjects. The aim of the research is to develop alternative activities for helping students in the seventh grade of middle school develop their views on the nature of science and for better teaching the nature of science. In this study, four different activities suitable for middle school seventh class achievements which are also related to the nature of science were developed and worksheets related to those activities were prepared. The activities and worksheets were examined by two science education experts and necessary arrangements were made in line with their opinions. These events are called; "mystery candle inbox", "following trail", "mystery in box", and "Colorful lights" activity. This study was designed according to case study settings from qualitative research methods. The research group consists of 27 students who are in the seventh grade of a middle school in Kırşehir. When the activities are being carried out, students filled in worksheets for each activity. The worksheets were analyzed by content analysis method. At the end of the research, it was determined that the designed and applied the nature of science activities have a positive effect on the development of the students' opinions about the nature of science.